Analysis of the Surroundings of the Passo Fundo-RS Bus Terminal According to PNDU Guidelines and Municipal Laws - Alves, Laira Kichel; Silva , Thaísa Leal da (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – To analyze the surroundings of the Bus Terminal in the city of Passo Fundo-RS, according to selected variables from the National Urban Development Policy (PNDU) and Municipal Laws, such as the Integrated Development Master Plan, Mobility Plan, and Building Code. Methodology – Initially, a documentary analysis was carried out on the National Urban Development Policy and the municipal laws of Passo Fundo. Subsequently, an on-site visit to the bus terminal was carried out to collect data and make photographic records focusing on the selected PNDU variables for analysis. After analyzing the data, maps were developed for each analyzed point using QGIS software, including proposals for improvements at these locations. Results – As results, the road network and waste collection maps show all the locations where services are offered around the Bus Terminal and propose ways they could be improved. The leisure and accessibility maps complement each other, since users need adequate conditions to move safely between spaces around the Terminal. The active mobility map shows great potential to expand the connection of city bike lanes to the bus terminal, encouraging bicycle use and shared bike stations. In addition to the developed maps, this research also presented suggestions based on the PNDU variables, which could be applied for the urban development of the municipality. Originality/Relevance – Studies on urban development in Brazil mostly focus on capitals and large urban centers, with few analyses directed at medium-sized cities such as Passo Fundo. Thus, this study promotes the application of National Urban Development Policy (PNDU) variables at the local scale, correlating them with municipal legislation. This perspective highlights an underexplored aspect in academic research and presents practical solutions to evaluate and improve urban policies in similarly sized cities. Theoretical/Methodological Contributions – The analysis enables the construction of a replicable evaluation model, allowing the developed methodology to be applied in other cities. Social and Environmental Contributions – The study aims to reduce social inequality and improve accessibility, especially for the Passo Fundo Bus Terminal and its surroundings. Complementarily, it contributes to creating more inclusive and sustainable environments by proposing improvements in the urban space.